Swift observations of GS 1826−238. Issue 2 (13th November 2017) - Ji, L.; Santangelo, A.; Zhang, S.; Ducci, L.; Suleimanov, V.
Abstract: GS 1826−238 is a well-studied low-mass X-ray binary neutron star. This source was in a persistent hard state since its discovery in 1988 and until 2014 June. After that, the source exhibited several softer periods of enhanced intensity in the energy range 2–20 keV. We studied the long-term light curves of MAXI (Monitor of All Sky X-ray Image) and Swift /BAT, and found clearly two branches in the MAXI–BAT and hardness–intensity diagrams, which correspond to the persistent state and softer periods, respectively. We analysed 21 Swift /XRT observations, of which four were located in the persistent state while the others were in softer periods or in a state between them. The XRT spectra could be generally fitted by using an absorbed Comptonization model with no other components required. We found a peculiar relationship between the luminosity and the hardness in the energy range of 0.6–10 keV: when the luminosity is larger (smaller) than 4 per cent–6 per cent  L edd, the hardness is anti-correlated (correlated) with luminosity. We also estimated the variability for each observation by using the fractional rms in the 0.1–10 Hz range. We found that the observations in the persistent state had a large fractional rms of ∼25 per cent, similar to other low-mass X-ray binaries. However, the variability is mainly found in the range of 5 per cent–20 per cent during softer periods. We suggest that GS 1826−238 did not evolve into the soft state of atoll sources, and all the observed XRT observations during the softer periods resemble a peculiar intermediate state of atoll sources.